On some common objections to a behavioral approach to psychological categories. (2nd April 2016) - Lazzeri, Filipe
Abstract: This paper addresses several objections that have been leveled against a behavioral approach to psychological categories. It reconstructs and critically assesses (a) the so-called causal objection; (b) alleged counterexamples whereby one can exhibit the typical behaviors associated with a psychological phenomenon without exhibiting the latter, including Lewis' "perfect actor" case and Kirk's "zombie"; (c) alleged counterexamples whereby organisms can exemplify psychological phenomena without exhibiting any behavior associated with them, including Armstrong's imagined brain in a vat, Putnam's "super-super-spartans" scenario, and related cases; and (d) the holistic objection. Mistaken assumptions in each of these objections are pinpointed. The paper starts with a brief characterization of behaviorism about psychological categories and a summary of the particular version thereof supported here, which draws upon Ryle and Skinner, among others.